DEMOGRAPHIC POTENTIAL OF THE CARPATHIAN REGION OF UKRAINE: SCENARIO MODELING - BARANYAK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the current state and trends of the population reproduction of the Carpathian region of Ukraine. The values of the key indicators of demographic reproduction in the section of the constituent components (number and age structure of the population, birth rate, mortality, migration) were monitored. It is summarized that the narrowed type of reproduction of the population of the Carpathian region is largely explained by the extremely low values of fertility indicators and the high level of mortality, which in 2020-2021 significantly accelerated the rate of polarization of values as a result of the negative impact of the COVID-19 pandemic. The revealed tendencies of the natural reproduction of the population of the Carpathian region testify to the fact of weak and inefficient use of the available reproductive potential of youth, and also substantiate the hypothesis of a high probability of strengthening depopulation processes in the regions of the Carpathian region and aggravation of demographic problems in the near future. The fundamentals of the theoretical population forecasting model are presented, which includes three interrelated blocks of forecast indicators - birth rate, mortality rate, and migration rate. Based on the change of these indicators, the forecast guidelines for the demographic development of the Carpathian region until 2050 are outlined. In particular, with the preservation of the current trends of natural demography (ultra-low values of birth rate and life expectancy) and zero migration balance in conditions of inevitable further transformation of the age structure, the number of inhabitants of the Carpathian region in 2022-2050 may decrease by 934 thousand people or 16 %. If the values of indicators of demo-reproducing processes improve according to an unlikely optimistic scenario of the development of demographic event, the number of residents of the Carpathian region may decrease by 144 thousand. As a result of scenario modeling, the practical results of demographic forecasting are presented in three versions (pessimistic, trend and optimistic) and can be used in the formation of directions for the development of regional demographic policy.